( a 1 + 4 ) ( a 2 + 4 ) ( a 3 + 4 ) ( a 4 + 4 ) ( a 5 + 4 ) .
If a 1 , a 2 , a 3 , a 4 and a 5 are the fifth roots of 1088, then find the value of the expression above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
a 1 , a 2 , a 3 a 4 , a 5 are the roots of the equation x 5 = 1 0 8 8
By this we get that a 1 . a 2 . a 3 . a 4 . a 5 = 1 0 8 8
The Given expression can be simplified to get 4 5 + 4 4 ( a 1 + a 2 + a 3 + a 4 + a 5 ) + . . . . . . . . . . . . . + a 1 . a 2 . a 3 . a 4 . a 5
All terms will become zero acc. to x 5 = 1 0 8 8 except first and the last term.
So the result obtained will be = 4 5 + 1 0 8 8
= 2 1 1 2
Would you please elaborate & explain how you get the last expression (4^5+.......+). and arrive at subsequent conclusion?
Log in to reply
When you expand the product you'll have a series of terms. Each term in the expansion will have a contribution from each product.
For the term consisting of none of the ai terms, the only way to do this is to get all of the 4 => 4^5.
If you want a term with nothing but ai terms, the only way to do this is to multiply all of the ai terms => a 1*a 2 a_3 a 4*a 5
Now for the stuff in between ...
Recall that you have take something from each of the product terms. Therefore if you want all of the terms with two ai terms, then you have to take the 4 from the other three things in the product.
By Vieta's formula, that the "stuff in between" is all 0 and so you therefore get what Shubhendra says.
same method
There's a typo in the problem, last bracket should be ( a 5 + 4 ) .
Let us define
f ( x ) = x 5 − 1 0 8 8 1 .
Then f ( a 1 ) = f ( a 2 ) = f ( a 3 ) = f ( a 4 ) = f ( a 5 ) = 0 , since a 1 , a 2 , a 3 , a 4 , a 5 are the roots of the equation x 5 − 1 0 8 8 = 0 .
However we can also factorise the polinomial x 5 − 1 0 8 8 in terms of its roots as
f ( x ) = ( x − a 1 ) ( x − a 2 ) ( x − a 3 ) ( x − a 4 ) ( x − a 5 ) 2 .
Using 2 , we now write
f ( − 4 ) = − ( 4 + a 1 ) ( 4 + a 2 ) ( 4 + a 3 ) ( 4 + a 4 ) ( 4 + a 5 ) ,
Alternatively, using the 1 ,
f ( − 4 ) = ( − 4 ) 5 − 1 0 8 8 = − 2 1 1 2 .
And that's the end of the story.
As a side note, we can write 1 0 8 8 = 1 0 2 4 + 6 4 = 2 1 0 + 2 6 = 2 1 0 ( 1 + 2 − 4 ) . Since for the sake of estimation, we note that 2 − 4 ≪ 1 . Then 1 0 8 8 ≈ 2 1 0 , so the real fifth root of 1088 is very close to 4.
Problem Loading...
Note Loading...
Set Loading...
Note that a 1 , a 2 , a 3 , a 4 , a 5 are the roots of the equation x 5 − 1 0 8 8 = 0 . Hence, the ( a i + 4 ) 's are the roots of the equation ( x − 4 ) 5 − 1 0 8 8 = 0 , x 5 + ⋯ − 2 1 1 2 = 0 . Since the product of the roots of the equation above is given by − ( − 2 1 1 2 ) / 1 = 2 1 1 2 , the desired product is 2 1 1 2 .